Studies concerning the anion ex-change resins catalyzed esterification of epichlorohydrin with organic acids - E.I. Muresan (Chemical Industry and Chemical Engineering Quarterly, 2009)
The paper studies the esterification of carboxylic acids with epichlorohydrin over two macroporous strong base anion exchange resins with different polymer matrix. For both resins, the influence of reaction parameters (temperature, catalyst loading, molar ratio) on the reaction rate and the yields of the two isomeric esters were investigated.